Concurrent hollow and visceral organs traumatic injury secondary to metal shrapnel penetration in a male with situs inversus totalis: A case report - Mohd Firdaus Che Ani; Muhammad Aizat Tamlikha Ismail; Nor Faezan Abdul Rashid; Firdaus Hayati (Elsevier Ltd, 2022)
Situs inversus totalis (SIT) develops as a result of the embryological developmental anomaly. Managing this condition surgically is challenging as the anatomy will be mirror-imaged. A 42- year-old male had metal shrapnel broken loose from a hammer-head metal piece and pierced into his upper abdomen. A computed tomography scan of the abdomen revealed SIT with evidence of solid foreign body artefacts which were seen piercing through segment VIII of the liver and the anterior gastric wall. Exploratory laparotomy revealed a moderate amount of haemoperitoneum and a single perforation at the upper body of the stomach that was confirmed by on-table-endoscopy. The perforation was repaired with a modified Graham patch and the liver injury had stopped bleeding intraoperatively. The challenges arose during laparotomy assessment and endoscopic assessment due to inversed anatomy.